2001
DOI: 10.1007/s004410000335
|View full text |Cite
|
Sign up to set email alerts
|

Intrasexual and intersexual dimorphisms of the red salmon prosencephalon

Abstract: Intrasexual as well as intersexual dimorphisms were found in the prosencephalon and mesencephalon of adult Oncorhynchus nerka (red/sockeye salmon). These dimorphisms are concerned with the position of the preoptic nucleus, nucleus lateralis tuberis, habenula, third ventricle, tectal ventricles, preoptic recess, recessus lateralis, horizontal commissure, posterior commissure, and toral commissure. The intrasexual dimorphism was characterized by either a rostral ("r"-pattern) or a caudal ("c"-pattern) position o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 67 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…Intrasexual and intersexual dimorphisms have been demonstrated in the NPO of red salmon (Jadhao et al 2001). Earlier studies on goldfish did not report any sexual dimorphism (Olivereau and Olivereau 1991a), whereas a more recent study has revealed GAL-ir perikarya within and lateral to the NPO only in males (Prasada Rao et al 1996).…”
Section: Discussionmentioning
confidence: 95%
“…Intrasexual and intersexual dimorphisms have been demonstrated in the NPO of red salmon (Jadhao et al 2001). Earlier studies on goldfish did not report any sexual dimorphism (Olivereau and Olivereau 1991a), whereas a more recent study has revealed GAL-ir perikarya within and lateral to the NPO only in males (Prasada Rao et al 1996).…”
Section: Discussionmentioning
confidence: 95%
“…When the same cell appeared in more than one micrograph, we measured the largest cell section by using the Leica Application Suite. Because the cell shape often seemed not to be round in the sections, we calculated the mean between the long and the short axes (see Jadhao et al 2001).…”
Section: Methodsmentioning
confidence: 99%
“…However, these observations are not surprising, because the brain could respond to environmental variations through rapid adaptive mechanisms, whereby different types of brain organization could be observed in closely related species within a subgroup of vertebrates, with respect to different life histories (Northcutt, ; Kolm et al, ), or even in the same species. In this regard, one of the most common differences in brain anatomy concerns sexual dimorphism (Morris et al, ); in some cases, up to four different types of preoptic nucleus morphologies have been described in the same species (Jadhao et al, ). Of course this strong adaptive brain plasticity can make brain comparisons difficult for evolutionary purposes, because some adaptations can originate in a species as a response to a contingent environmental request, and thus do not reflect the real evolutionary history.…”
mentioning
confidence: 99%